A Review on the State of the Art of the Transformerless Converters for PV Systems - Siddiqui, Mohd Imran; Asim, Mohammed; Hassan, Hanzala (EAI Endorsed Transactions on Energy Web, 2026)
Transformerless converters for PV systems have been a field of interest for researchers for decades. The transformers make the system bulky, costly, and inefficient. With the advancement of photovoltaic and power electronic technology, it was hoped to eliminate the transformer. Constraints were posed in the form of ratings for semiconductor devices, PV source voltage requirements, efficiency, filter size, THD, and, most importantly, the leakage current problem in a grid-connected PV system. The smart grid aimed to incorporate distributed energy resources, which led to grid-connected PV systems. So, new topologies were proposed, and isolated converters evolved over time. Transformerless inverter topologies aim to address leakage current issues without using isolation transformers. The objective of this paper is to present a review and comparison of existing transformerless converters, with a focus on inverter topologies for leakage current reduction, based on major technical parameters, in a way that is helpful for seekers to readily find information. Most recent developments have been incorporated.